2019
DOI: 10.3390/nano9111540
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Chemo- and Photodynamic Therapies with C60 Fullerene-Doxorubicin Nanocomplex

Abstract: A nanosized drug complex was explored to improve the efficiency of cancer chemotherapy, complementing it with nanodelivery and photodynamic therapy. For this, nanomolar amounts of a non-covalent nanocomplex of Doxorubicin (Dox) with carbon nanoparticle C60 fullerene (C60) were applied in 1:1 and 2:1 molar ratio, exploiting C60 both as a drug-carrier and as a photosensitizer. The fluorescence microscopy analysis of human leukemic CCRF-CEM cells, in vitro cancer model, treated with nanocomplexes showed Dox’s nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 76 publications
(158 reference statements)
0
18
0
Order By: Relevance
“…The FU-DOX and FA-FU-DOX conjugates exhibited higher fluorescence intensity than free DOX, especially at 1 h incubation time, indicating a higher amount of cellular uptake than that for free DOX. It may be explained that the intracellular drug accumulation was efficiently promoted by the FU carrier at the experimental conditions ( Grebinyk et al, 2019 ). Moreover, FA-FU-DOX showed the best cellular uptake in FR-positive BEL-7402 cells but it did not exhibit significant higher accumulation than FU-DOX in FR-negative HepG2 and L02 cells ( Figure 5 ), which suggested that the attachment of FA to FU-DOX enhanced the uptake of the conjugates into FR-positive cells via an FR-mediated endocytic process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FU-DOX and FA-FU-DOX conjugates exhibited higher fluorescence intensity than free DOX, especially at 1 h incubation time, indicating a higher amount of cellular uptake than that for free DOX. It may be explained that the intracellular drug accumulation was efficiently promoted by the FU carrier at the experimental conditions ( Grebinyk et al, 2019 ). Moreover, FA-FU-DOX showed the best cellular uptake in FR-positive BEL-7402 cells but it did not exhibit significant higher accumulation than FU-DOX in FR-negative HepG2 and L02 cells ( Figure 5 ), which suggested that the attachment of FA to FU-DOX enhanced the uptake of the conjugates into FR-positive cells via an FR-mediated endocytic process.…”
Section: Resultsmentioning
confidence: 99%
“…The administration of fullerene alone before DOX administration or complexed with DOX via non-covalent bonds could diminish DOX-induced acute toxicity in the heart or liver ( Borović et al, 2014 ; Seke et al, 2016 ; Jacevic et al, 2019; Petrovic et al, 2018 ). More importantly, fullerene can act as a transporter for anticancer drugs, such as DOX ( Grebinyk et al, 2019 ; Kazemzadeh and Mozafari, 2019 ). These biological properties of fullerenes and the potential ability to carry drugs make it attractive to be applied in the drug delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to fullerene and antenna nanoparticles (DA NPs), DAF NPs showed better reactive oxygen species and heat generation efficacy. In vitro and in vivo studies demonstrated that DAF NPs could effectively inhibit tumor growth through synergetic PDT and PTT [ 150 ]. As a nanocarrier, fullerene has also been used in chemical drug delivery combined with PDT or PTT [ 150 , 151 ].…”
Section: Nanomaterials Used For Cancer Treatmentmentioning
confidence: 99%
“…C 60 fullerene reduces lipid peroxidation by actively absorbing ROS [35]. C 60 fullerenes can penetrate the cell membrane and localize in the mitochondria [36,37], which are the source of ROS during the development of ischemic cell damage. Finally, the obtained above results are also confirmed by the previously obtained data on the effect of water-soluble C 60 fullerenes on the functions of the antioxidant systems of the body in inflammatory and pathological processes [38][39][40][41].…”
Section: Blood Biochemical Indicators Of Rats With Injured Musclementioning
confidence: 99%